Potential and characteristics of dadiah processed into products-like nuggets with addition of cinnamon bark flour (Cinnamomum burmanni). Issue 1 (November 2021) - Sandra, A; Purwati, E; Hasibuan, A
Abstract: Dadiah is a natural fermentation of buffalo milk from West Sumatra, which has a distinctive smell and flavor. This causes the dadiah to be less liked, so it is necessary to diversify the processed of dadiah. This study aimed to determine the effect of adding cinnamon flour (Cinnamomum burmanni) in the processing of nugget-like products on antioxidants, cholesterol, the total colony of lactic acid bacteria and organoleptic values. This research used 2000 grams of dadiah and cinnamon bark flour (15 g). The variables observed were antioxidants, cholesterol, the total colony of lactic acid bacteria and organoleptic values. The method used in this study was an experimental method using a Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatments in this study were the addition of cinnamon flour namely A (0%), B (0.5%), C (1%), D (1.5%). The results of this study indicated that the addition of cinnamon flour to nugget-like products had a significant effect (P<0.05) increasing antioxidant levels and decreasing cholesterol levels, not significantly different (P> 0.05) on the total colony test of lactic acid bacteria and the organoleptic test of taste, texture and flavor. The addition of cinnamon flour to nugget-like products in treatment D (1.5%) gave the best results with antioxidant levels of 73.24%, cholesterol levels of 20.32 mg/dl, the total colony of lactic acid bacteria 1.48x10 7 CFU / ml and taste organoleptic value 3.44, texture 3.68 and flavor 3.80.